Prevalence and factors associated with retinopathy in patients of the integral diabetes program of the san genaro de villa Chorillos health center, Lima-Peru: Prevalencia de Retinopatia en pacientes del programa integral de diabetes del centro de Salud San Genaro de Villa, Chorillos - Longa-López, John (2022)
Objectives: To determine the prevalence and factors associated with retinopathy in patients of the Comprehensive Diabetes Program of the San Genaro Health Center in Villa Chorrillos. Methods: Descriptive, observational, cross-sectional, prospective study; with a sample of 119 adults and older adults. Non-probabilistic convenience sampling was used. The variables studied were diabetic retinopathy, type of diabetic retinopathy, degree of diabetic retinopathy, age, sex, educational level, time of illness, time belonging to the program, type of treatment, personal history of arterial hypertension, personal history of dyslipidemia, mean systolic blood pressure (SBP), mean diastolic blood pressure (DBP), Body Mass Index (BMI), Glycosylated Hemoglobin (HbA1c), Total Cholesterol, LDL Cholesterol, HDL Cholesterol, Triglycerides, creatinine clearance, microalbuminuria, visual efficiency of Snell-Sterling, associated ocular pathology and ocular pressure. Descriptive statistical methods were used. Results: The prevalence of diabetic retinopathy (DR) was 15.1%, of which 77.8% is nonproliferative RD and 22.2% proliferative RD. In relation to the degrees in Non-Proliferative DR, 64.3% is mild and 35.7% moderate; and in Proliferative DR, 25% is early, 25% high risk and 50% severe. The biochemical value that showed a considerable difference was microalbuminuria, reaching a value of 356.9 mg/dl/24hrs. Conclusions: The prevalence of retinopathy is 15.1%, of which 77.8% is non-proliferative retinopathy and 22.2% proliferative retinopathy and the associated factors were systolic blood pressure (p<0.001) and microalbuminuria(p<0.001).